2002
DOI: 10.1002/mds.10142
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of dystonia: A neuronal model

Abstract: Dystonia has commonly been thought to represent a disorder of basal ganglia function. Although long considered a hyperkinetic movement disorder, the evidence to support such a classification was based on the presence of excessive involuntary movement, not on physiological data. Only recently, with the return of surgical procedures using microelectrode guidance for the treatment of dystonia, has electrophysiological data demonstrated an alteration in mean discharge rate, somatosensory responsiveness and the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
151
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(167 citation statements)
references
References 92 publications
14
151
2
Order By: Relevance
“…Based on pharmacologic studies, there seems to be a relative increase in the activity of striatal neurons of the direct pathway over those that give rise to the indirect pathway in dystonia [195,196], and single-cell recording studies in patients undergoing functional neurosurgical treatments have demonstrated low discharge rates in both GPe and GPi [197][198][199][200][201][202], in distinction to the aforementioned changes in PD where GPi discharge rates are generally increased. The presence of lowfrequency discharge in the GPi in patients with dystonia is similar to that in other hyperkinetic disorders, including chorea/ ballismus and motor tics [197,203,204].…”
Section: Dystoniamentioning
confidence: 99%
“…Based on pharmacologic studies, there seems to be a relative increase in the activity of striatal neurons of the direct pathway over those that give rise to the indirect pathway in dystonia [195,196], and single-cell recording studies in patients undergoing functional neurosurgical treatments have demonstrated low discharge rates in both GPe and GPi [197][198][199][200][201][202], in distinction to the aforementioned changes in PD where GPi discharge rates are generally increased. The presence of lowfrequency discharge in the GPi in patients with dystonia is similar to that in other hyperkinetic disorders, including chorea/ ballismus and motor tics [197,203,204].…”
Section: Dystoniamentioning
confidence: 99%
“…Recent electrophysiological studies have attributed dystonia to an altered pattern of pallidal output with burst firing and highly irregular interspike frequencies. 32,33 If present to a lesser degree in nonmanifesting dystonia gene carriers, this subcortical noise source may interfere with the functioning of corticostriatopallidothalamocortical and related pathways, and with associated aspects of motor behavior including the learning of sequences. Nonetheless, the possibility of an inherent genetically mediated abnormality in frontostriatal connectivity cannot be excluded.…”
Section: Brain Activationmentioning
confidence: 99%
“…It is usually bilateral, although it may be unilateral briefly at onset. [1][2][3] Initial symptoms include unpleasant sensations, eyelid fluttering, and increased blink rate in response to stimuli, progressing eventually to chronic involuntary spasms in both eyes. 4 Quality of life may be significantly impaired, with increased difficulty in reading, writing, and driving.…”
Section: Introductionmentioning
confidence: 99%